Internalizing Islamic moderation: a model approach for educational institutions - Kuswanto, Edi; Mubin, Muhammad Nurul; Suharsono; Kurniawan, Dwi Setia (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
This paper examines the methods of internalizing the value of moderation in Islamic education, specifically within the context of at-tawāsuṭ wal i’tidāl (moderation and justice) in schools, drawing on Thomas Lickona's character education theory. The research methodology employed in this study includes a literature review and a survey. Although the survey presents some numerical data, the overall study is qualitative. The findings show that the core value of moderation in the Nahdlatul Ulama is at-tawāsuṭ wal i’tidāl, which will spell out various values of moderation derivatives. The processes of internalizing such Islamic moderation in schools – in the perspective of Lickona- were done along three stages: 1) Knowing, conducted through TCL (Teacher-Centered Learning) strategy by applying CTL (Contextual Teaching and Learning) approach and group discussion method; 2) Feeling, achieved through strengthening intra classroom activities, editing, and habituating; and 3) Doing, which is more implemented in intra and extracurricular activities. This research offers insights into internalizing Islamic moderation in schools, drawing on the perspective of at-tawāsut wal i’tidal and Lickona's character education theory. It contributes to the formulation of a model approach that can be implemented by various educational institutions, particularly schools, to foster Islamic moderation among students.